2002
DOI: 10.1039/b209696j
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase chemistry of the 2-tert-butyl-3-phenylphosphirenylium cation: novel onium ions by nucleophilic attack at phosphorus and de novo P-spiro bicyclic phosphonium ions via [4 + 2+] cycloaddition with dienes

Abstract: The 2-tert-butyl-3-phenylphosphirenylium ion 13 is formed in abundance in the gas phase from 1-chloro-1H-phosphirene 6 upon 70 eV electron ionization. Collision-induced dissociation (CID) and ion-molecule reactions followed by CID of the product ions were performed via pentaquadrupole mass spectrometry to probe the structure and reactivity of 13 towards representative nucleophiles and dienes. Under CID conditions, 13 produces a variety of fragment ions mainly via dissociation processes that are preceded by iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Mass spectrometric techniques have been used to probe the reactions of (272) with nucleophiles and dienes. 779 Phosphenium cations, R 2 P: 1 , are believed to be formed as intermediates in the exchange reactions of the phosphirenium salt (273) with alkynes, to give new phosphirenium salts, e.g., (274). 780 The 2-(phosphirenyl)ethylphosphinidene (275) (generated by thermolysis of a related 2-(phosphirenyl)ethylphosphole in the presence of dimethyl acetylenedicarboxylate) undergoes a selfcondensation to give the 2,4-diphosphabicyclobutane (276).…”
Section: Phosphirenes Phospholes and Phosphininesmentioning
confidence: 99%
“…Mass spectrometric techniques have been used to probe the reactions of (272) with nucleophiles and dienes. 779 Phosphenium cations, R 2 P: 1 , are believed to be formed as intermediates in the exchange reactions of the phosphirenium salt (273) with alkynes, to give new phosphirenium salts, e.g., (274). 780 The 2-(phosphirenyl)ethylphosphinidene (275) (generated by thermolysis of a related 2-(phosphirenyl)ethylphosphole in the presence of dimethyl acetylenedicarboxylate) undergoes a selfcondensation to give the 2,4-diphosphabicyclobutane (276).…”
Section: Phosphirenes Phospholes and Phosphininesmentioning
confidence: 99%
“…Eberlin and co-workers studied several cycloaddition reactions of N-acyliminium, 153 acylium, 154 and phosphirenylium ions. 155 The reactions of (CH 3 ) 3 NCLO 1 , PhCLO 1 , (CH 3 ) 2 NCLS 1 , CH 3 CLO 1 , CH 3 CH 2 CLO 1 , CH 2 CHCLO 1 , and several 2-azabutadienyl cations with 1-oxy-substituted 1,3-dienes and ethyl vinyl ether were carried out. Structurally diagnostic chemistry was observed for N-H, N-alkyl, and N-aryl 2-azabutadienyl cations.…”
Section: (9)mentioning
confidence: 99%
“…These studies have revealed new reactions and shed light to intrinsic reactivity and reaction mechanisms, and important analytical and synthetic uses for these ion/molecule reactions have been found. The intrinsic (free of solvent and counter ion effects) concerted or stepwise polar cycloaddition reactivity of many classes of gaseous ions have been investigated such as for ionized alkenes, fullerenes, ylides, nitrilium and immonium ions, hetarynium ions, cyclic N‐acyl and N, N‐diacyliminium ions, the nitronium ion, protonated and methylated azabutadienes, phosphenium ions, phosphirenylium ion, ionized α‐oxoketene and the phenyl sulfinyl cation . Perhaps, the most systematically studied class of gas‐phase polar cycloadditions has been the [4 + 2 + ] cycloadditions involving acylium ions (R‐C + = O) and dienes or heterodynes .…”
Section: Introductionmentioning
confidence: 99%